Serum Preadipocyte Factor-1 Concentrations in Females with Obesity and Type 2 Diabetes Mellitus: The Influence of Very Low Calorie Diet, Acute Hyperinsulinemia, and Fenofibrate Treatment - Kavalkova, P.; Touskova, V.; Roubicek, T.; Trachta, P.; Urbanova, M.; Drapalova, J.; Haluzikova, D.; Mraz, M.; Novak, D.; Matoulek, M.; Lacinova, Z.; Haluzik, M. (Hormone and Metabolic Research, 2013)
Appropriate differentiation capacity of adipose tissue significantly affects its ability to store lipids and to protect nonadipose tissues against lipid spillover and development of insulin resistance. Preadipocyte factor-1 (Pref-1) is an important negative regulator of preadipocyte differentiation. The aim of our study was to explore the changes in circulating Pref-1 concentrations in female subjects with obesity (OB) (n=19), females with obesity and type 2 diabetes mellitus (T2DM) (n=22), and sex- and age-matched healthy control subjects (C) (n=22), and to study its modulation by very low calorie diet (VLCD), acute hyperinsulinemia during isoglycemic-hyperinsulinemic clamp, and 3 months’ treatment with PPAR-α agonist fenofibrate. At baseline, serum Pref-1 concentrations were significantly higher in patients with T2DM compared to control group, while only nonsignificant trend towards higher levels was observed in OB group. 3 weeks of VLCD decreased Pref-1 levels in both OB and T2DM group, whereas 3 months of fenofibrate treatment had no significant effect. Hyperinsulinemia during the clamp significantly suppressed Pref-1 levels in both C and T2DM subjects and this suppression was unaffected by fenofibrate treatment. In a combined population of all groups, circulating Pref-1 levels correlated positively with insulin, leptin and glucose levels and HOMA (homeostasis model assessment) index. We conclude that elevated Pref-1 concentrations in T2DM subjects may contribute to impaired adipose tissue differentiation capacity associated with insulin resistance in obese patients with T2DM. The decrease of Pref-1 levels after VLCD may be involved in the improvement of metabolic status and the amelioration of insulin resistance in T2DM patients.
Keywords: Pref -1; insulin resistance; very low calorie diet; isoglycemic hyperinsulinemic clamp; fenofibrate